2004
DOI: 10.1016/j.clinph.2004.02.015
|View full text |Cite
|
Sign up to set email alerts
|

ERP evidence of impaired central nervous system function in virally suppressed HIV patients on antiretroviral therapy

Abstract: Objective-To examine the effects of human immunodeficiency virus (HIV) on central nervous system (CNS) function in patients receiving antiretroviral therapy (ART) who have suppressed viral loads.Methods-Event-related brain potentials (ERPs) were recorded from 15 virally suppressed HIV patients and 15 age-, sex-, and education-matched controls while they performed a 3-stimulus auditory oddball task. The amplitude and latency of the P3a, P3b, and early auditory components were examined in HIV patients and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
2
23
1
1
Order By: Relevance
“…This data agrees with the research by Chao et al (25) that also found disorders in this potential with HIV/AIDS individuals. According to Picton (18) the P300 amplitude is not a reliable parameter to compare the potentials between two groups because it may influenced by attention factors.…”
Section: Discussionsupporting
confidence: 83%
“…This data agrees with the research by Chao et al (25) that also found disorders in this potential with HIV/AIDS individuals. According to Picton (18) the P300 amplitude is not a reliable parameter to compare the potentials between two groups because it may influenced by attention factors.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have documented disorders in the auditory evoked potentials of patients with AIDS (Martin et al, 2001;Polich & Basho, 2002;Chao et al, 2004;Tartar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Before higher level cognitive symptoms manifest, the early stages of HIV-1 may be marked by alterations in temporal processing, as assessed with amplitude and latency measures of auditory evoked potentials (AEPs), both without (Castello et al 1998;Fein et al 1995;Gil et al 1992;Koralnik et al 1990;Pagano et al 1992;Schroeder et al 1996;Vigliano et al 2000), and after, CART initiation (Chao et al 2004;Matas et al 2010). Simian and feline immunodeficiency virus models have also demonstrated alterations in evoked potentials (Phipps et al 2000;Prospero-Garcia et al 1999;Raymond et al 1998;Riazi et al 2009).…”
Section: Introductionmentioning
confidence: 99%